Antecedents and Outcomes of Employee Brand Knowledge: A Literature Review - Fathya, Vita Nurul (JDM (Jurnal Dinamika Manajemen), 2021)
Various literature states that employee knowledge about brands is a major determinant of the success of the services provided by the organization. Therefore, employee knowledge about brands is important to understand, especially related to the antecedents and results of that knowledge. Although there have been studies that discuss employee knowledge about brands, antecedents, and results of employee knowledge about brands are still widespread in various studies. The purpose of this paper is to review the literature relating to employee knowledge about brands and propose a future research agenda related to this topic. The method is identifying previous literatures which investigated the topic. The findings show that there are several antecedents and the results of employee knowledge about brands that have been studied in the literature. This literature review concludes that future research can discuss various antecedents and results of employee knowledge about brands that have not been discussed in the research of the reviewed literature.Ã‚Â